2012
DOI: 10.1093/mnras/sts383
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution spectropolarimetric survey of Herbig Ae/Be stars – I. Observations and measurements★

Abstract: This is the first in a series of papers in which we describe and report the analysis of a large survey of Herbig Ae/Be stars in circular spectropolarimetry. Using the ESPaDOnS and Narval high-resolution spectropolarimeters at the Canada-France-Hawaii and Bernard Lyot Telescopes, respectively, we have acquired 132 circularly-polarised spectra of 70 Herbig Ae/Be stars and Herbig candidates. The large majority of these spectra are characterised by a resolving power of about 65,000, and a spectral coverage from ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
249
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(262 citation statements)
references
References 158 publications
(318 reference statements)
12
249
0
1
Order By: Relevance
“…The stellar rotation of V1026 Sco is v sin i = 65.3 ± 3.1 km s −1 (Alecian et al 2013a), leading to a maximum rotational velocity of ∼86 km s −1 if the inclination of the star is comparable to the disk inclination. This is similar (Boehm & Catala 1995) or slightly lower (Alecian et al 2013b) than the average velocity of low-mass Herbig Ae/Be stars but higher than measurements of T Tauri stars (Weise et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stellar rotation of V1026 Sco is v sin i = 65.3 ± 3.1 km s −1 (Alecian et al 2013a), leading to a maximum rotational velocity of ∼86 km s −1 if the inclination of the star is comparable to the disk inclination. This is similar (Boehm & Catala 1995) or slightly lower (Alecian et al 2013b) than the average velocity of low-mass Herbig Ae/Be stars but higher than measurements of T Tauri stars (Weise et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors find slightly different parameters for the alternative distance of 145 ± 20 pc. For example Alecian et al (2013a) Meeus et al (1998); (b) Folsom et al (2012); (c) Mendigutía et al (2011). VLTI/AMBER and archival mid-infrared (MIR) VLTI/MIDI measurements into account. We describe our observations and the data reduction in Sect.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stable and large scale fields are called fossil fields (i.e. they are not continuously maintained from dissipation, Cowling 1945Cowling , 1953Borra et al 1982) and are observed in intermediate-mass stars from the premain-sequence phase (in Herbig Ae/Be stars), throughout the main-sequence phase, and very likely even until the red giant phase of stellar evolution (Aurière et al 2008(Aurière et al , 2011Alecian et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Ferrario et al 2009). The intermediate-mass stars show a magnetic fraction during their pre-main sequence evolution similar to Herbig stars (e.g., Hubrig et al 2009Hubrig et al , 2013, and references therein; Alecian et al 2013) as their main-sequence descendants, which may speak for fossil fields. On the other hand, there are almost no close binaries amongst the magnetic intermediate-mass main-sequence Ap-type stars (e.g.…”
Section: Introductionmentioning
confidence: 99%